"Worden als een kind". Als welk kind? - Meulen, Harry van der (Hervormde teologiese studies, 1996)
'Becoming like a child'. Like what child?. 'Becoming like a child' is an idea often expressed in the New Testament in connection with the following of Jesus. However, the meaning of this phrase is not so clear. It has' to be understood in its cultural context. The author seeks to clarify that cultural context by discussing the culture-related views of childhood in biblical - especially New Testament -times as these are refelcted in biblical, Qumran and early rabbinic literature.